Microencapsulated Piper colubrinum Volatiles as Sustainable Fruit Fly Attractants in Tropical Horticulture - Cico Jhon Karunia Simamora; Eva Pramuni Oktaviani Sitanggang; Febrina Feby (Universitas Panji Sakti, 2026)
Volatile compounds from tropical aromatic plants act as important semiochemical signals in agroecosystems, but their tendency to volatilize and oxidize limits their use as fruit fly attractants. This study developed a microencapsulation approach to stabilize Melada (Piper colubrinum) volatiles for practical field-level fruit fly attraction. A Completely Randomized Design (CRD) was employed, comprising four microencapsulation formulations with varying maltodextrin-gum arabic (MD-GA) ratios (2:10, 5:10, 10:10, and 12:10) and one petrogenol control, each replicated three times. Physicochemical properties and biological effectiveness were evaluated against fruit flies on chili pepper, guava, and papaya. Higher MD-GA ratios reduced surface oil content while improving encapsulation efficiency (EE), loading capacity (LC), and yield. Formulation F4 (12:10) performed best overall, with EE of 85.14%, LC of 1.39%, and yield of 82.38%, and was optimal for a wall structure giving strong volatile retention while sustaining adequate release for field attractiveness. Uniform microcapsule morphology confirmed good structural integrity, supporting sustained release under open field conditions. Field trials using 45 traps across three locations showed that encapsulated Melada volatiles effectively attracted Bactrocera umbrosa and Bactrocera melastomatos, remaining active up to 10 days longer than the petrogenol control, with F4 producing the highest catch across host plants and observation days. Attractiveness was highest on chili pepper, followed by guava and papaya, indicating synergy between host-plant volatiles and Melada's bioactive compounds. Overall, MD-GA microencapsulation enhances both the chemical stability and biological efficacy of Melada volatiles, showing strong potential as an eco-friendly attractant for sustainable fruit fly management in tropical horticulture.